2006
DOI: 10.1111/j.1556-4029.2006.00333.x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Suchey–Brooks Method for Aging Skeletons in the Balkans

Abstract: This study has been carried out to examine whether the Suchey-Brooks (S&B) methods could be successfully applied in age assessment of populations from the Balkans. The known-age sample consists of 33 females and 52 males pairs of pubic bones collected from the autopsy cases. Age estimation by S&B method showed an accuracy of 89.74% in males and 72.0% in females. Statistical analysis showed a positive correlation between the actual age of the investigated individuals and age phases obtained by the S&B method, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
38
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(44 citation statements)
references
References 13 publications
6
38
0
Order By: Relevance
“…Similar findings have been reported in previous investigations of age at death among Balkan populations: in Srebrenican population only 42.4% of individuals were accurately aged [13]; investigation on Serbian population showed that there were significant difference between real age of the individuals and the values derived from Suchey-Brooks [14] and Iscan and Loth [15] for older age categories of both males and females. Testing on other populations [16][17][18][19][20] also found poor performance in aging skeletal material due presumably to inter-population variation, indicating the necessity to introduce local anthropological standards for age assessment.…”
Section: Discussionsupporting
confidence: 87%
“…Similar findings have been reported in previous investigations of age at death among Balkan populations: in Srebrenican population only 42.4% of individuals were accurately aged [13]; investigation on Serbian population showed that there were significant difference between real age of the individuals and the values derived from Suchey-Brooks [14] and Iscan and Loth [15] for older age categories of both males and females. Testing on other populations [16][17][18][19][20] also found poor performance in aging skeletal material due presumably to inter-population variation, indicating the necessity to introduce local anthropological standards for age assessment.…”
Section: Discussionsupporting
confidence: 87%
“…Age was estimated for each individual using pubic symphysis (Brooks and Suchey, 1990) and auricular surface (Lovejoy et al, 1985). When each of these methods are used alone, they have a high rate of accuracy (72% for the pubic symphysis, Djurić et al, 2007;and 76% for the auricular surface, Bedford et al, 1993). When these two methods are used in conjunction, the reliability is even higher: 78% (Lovejoy et al, 1985;Ubelaker, 1989;Buikstra and Ubelaker, 1994).…”
Section: Age Estimation and Reliabilitymentioning
confidence: 98%
“…However, it is essential in physical anthropology and forensic and osteoarchaeological sciences. Most of the research formulating and evaluating skeletal aging techniques focused on the os coxae (i.e., auricular surface and pubic symphysis) have demonstrated low accuracy and high bias when the methodology is used on different populations [1][2][3][4][5][6][7][8][9][10][11][12][13]. These results have highlighted the necessity of increasing research to better understand age markers related to biology, designing new predictive models, and finding new age markers.…”
Section: Introductionmentioning
confidence: 98%